Preliminary phytochemical screenings and Pharmacological activities of Blumea lacera (Burn.f.) DC. - Khair, Md Abul; Ibrahim, Mohammed; Ahsan, Qamrul; Kuddus, Md Ruhul; Rashid, Ridwan Bin; Rashid, Mohammad Abdur (Dhaka University Journal of Pharmaceutical Sciences, 2015)
The methanol extract of the whole plant of Blumea lacera (Burn.f.) DC. (BLME) has been subjected to preliminary screenings for phytoconstituents and antipyretic, analgesic and anti-inflammatory activities. Antipyretic activity was assessed by the yeast-induced hyperthermia in mice. The analgesic property was evaluated by formalin-induced writhing test. Acetyl salicylic acid (ASA) was used as standard for in-vitro anti-inflammatory activity test. In yeast-induced pyrexia, the crude extract demonstrated a significant (p=0.05) reduction in body temperature of mice after elevation by the administration of yeast. These effects were pronounced at the 2nd and 3rd h of post-treatment with the extract. BLME exhibited a dose-dependent analgesic activity with 39.13% and 56.52% protection at 200-and 400-mg/kg, b.w., respectively as compared to 76.09% revealed by the standard diclofenac sodium. In the anti-inflammatory test, the crude extract at 400 ?g/ml displayed 62.40% inhibition of protein denaturation whereas standard acetyl salicylic acid exhibited 76.74% inhibition. Results of the preliminary phytochemical screenings demonstrated the presence of alkaloids, flavonoids and triterpenoids in the extract. DOI: http://dx.doi.org/10.3329/dujps.v13i1.21863 Dhaka Univ. J. Pharm. Sci. 13(1): 69-73, 2014 (June)